2015
DOI: 10.1007/s12012-015-9311-5
|View full text |Cite
|
Sign up to set email alerts
|

hERG Blockade by Iboga Alkaloids

Abstract: The iboga alkaloids are a class of naturally occurring and synthetic compounds, some of which modify drug self-administration and withdrawal in humans and preclinical models. Ibogaine, the prototypic iboga alkaloid that is utilized clinically to treat addictions, has been associated with QT prolongation, torsades de pointes and fatalities. hERG blockade as IKr was measured using the whole-cell patch clamp technique in HEK 293 cells. This yielded the following IC50 values: ibogaine manufactured by semisynthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…This observation goes along with noribogaine’s inhibitory action on hERG potassium channels (IC 50  = 3 µM: Fig. 2; [17]), which very closely resembles hERG inhibition by ibogaine [13, 14, 17]. It further provides an explanation for the delayed incidence of cardiac adverse events, which may occur even several days after ibogaine intake.
Fig.
…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…This observation goes along with noribogaine’s inhibitory action on hERG potassium channels (IC 50  = 3 µM: Fig. 2; [17]), which very closely resembles hERG inhibition by ibogaine [13, 14, 17]. It further provides an explanation for the delayed incidence of cardiac adverse events, which may occur even several days after ibogaine intake.
Fig.
…”
Section: Resultsmentioning
confidence: 66%
“…Up to now, the inhibition of currents through heterologously expressed hERG channels by ibogaine (IC 50 value, drug concentration needed for half-maximum inhibition = 3–4 µM [13, 14, 17]) remains the sole experimental evidence for the drug’s proarrhythmic potential in humans; data on human cardiomyocytes are still lacking. Moreover, two observations have cast reasonable doubts on ibogaine’s cardiotoxic effects: first, although hERG channel inhibition should retard AP repolarization, the drug significantly shortens AP duration in guinea pig ventricular cardiomyocytes [14]), a well-established model system for human myocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A special focus was given to plants containing alkaloids with reported cardiac side effects. Several studies have shown the hERG channel blocking potential of these nitrogen-containing compounds [6][7][8]25]. Recently, we reported on the development and experimental validation of several ligand-based hERG 3D-pharmacophore models [9].…”
Section: Resultsmentioning
confidence: 99%
“…Supporting information available online at http://www.thieme-connect.de/products prospectively and retrospectively [4][5][6][7][8]. In this view, in vitro/in vivo assays can be combined with in silico approaches allowing for the fast prediction of hERG channel blocking and providing insights into the ligand-target interaction at a molecular level [9][10][11][12].…”
Section: Hek293: Human Embryonic Kidney Cells Hergmentioning
confidence: 99%